Tomb Raider - West, Simon (Quezon City : Magnavision, 2001)
LARA CROFT, the world's most famous video-game heroine, bursts onto the big screen in"...the most stylish and entertaining action-adventure movie in years!" Exploring lost empires, finding priceless treasures, punishing villains in mortal combat... it's all in a day's work for adventurer Lara Croft (Angelina Jolie). But a secret from her father's (Jon Voight) past is about to lead lara to her greatest challenge: The Triangle of Light, a legendary artifact with the power to alter space and time. Lara must find the Traingle before it falls into the clutches of the Illuminati, a secret society bent on world domination. To stop the Illuminati, Lara will have to survive across-continental chase filled with unimaginable danger. But for the Tomb Raider, danger is the name of the game. With eye-popping action and electrifying thrills. TOMB RAIDER "will have you screaming, laughing and cheering from beginning to end"